The impact of the eastern Mediterranean teleconnection pattern on the Mediterranean climate - Hatzaki, M.a; Flocas, H.A.a; Giannakopoulos, C.b; Maheras, P.c (Journal of Climate, 2009)
The objective of this study is to investigate the impact of the eastern Mediterranean teleconnection pattern (EMP) on the present and future climate of the eastern Mediterranean during winter. For the present climate, daily precipitation and maximum and minimum surface temperature station data are employed for the period of 1958-2003. For the future climate, datasets of the same parameters are derived from the Hadley Centre Regional Climatic Model (HadRM3P) for the period of 2070-2100, using two Intergovernmental Panel on Climate Change (IPCC) emission scenarios for the evolvement of the future atmospheric concentrations of greenhouse gases. The investigation of the impact was based on the regularized canonical correlation analysis (RCCA), while qualitative estimations were performed for each phase of the pattern. It was found that the pattern indeed affects the mean winter patterns of temperature, precipitation, and their extreme events with inverse impacts between the two phases. More specifically, a positive phase of EMP is associated with a decrease in temperatures and an increase in precipitation, while the opposite occurs during the negative phase of EMP. In the future, the present impact according to each phase persists and intensifies in most of the cases. However, results are quite different between the two scenarios, because of the different estimated future shift of the EMP poles. © 2009 American Meteorological Society.
cited By (since 1996)16
Keywords: air-sea interaction; Atmospheric concentrations; Canonical correlation analysis; climate modeling; Climatic models; Climatology; correlation; Data-sets; Eastern mediterraneans; Electromagnetic pulse; Emission scenarios; estimation method; Extreme events; Future climates; global warming; greenhouse gas; Greenhouse gases; Intergovernmental panel on climate changes; Mediterranean climates; Mediterranean Sea; Minimum surfaces; Negative phase; precipitation (climatology); Qualitative estimations; Station datum; surface temperature; teleconnection; Teleconnection patterns